Political myopia, public debt, and economic growth - Raveh, O; Tsur, Y (University of Oxford, 2017)
Can economic growth increase public debt? Previous studies on the debt-growth nexus focused on the effects of debt on growth. We present an opposite perspective by showing that growth can reinforce deficit spending. A political economy model of endogenous public debt indicates that the underlying cause is political short-sightedness induced by reelection prospects. Reelection yields accountability but at the same time shortens incumbents' time horizon, giving rise to political myopia and the ensuing budget deficit bias. Our model shows that economic growth exacerbates this undesirable effect of reelection. We test the model's predictions using a panel of U.S. states over the period 1963-2007. Our identification strategy rests on constitutionally-entrenched differences in gubernatorial term limits that provide plausibly exogenous cross-state variation in political time horizon, and aggregate national TFP shocks that are exogenous to individual states. Our more conservative estimates indicate that over a course of five years, a one standard deviation positive TFP shock induces an increase of approximately $494 in real per capita public debt in politically myopic states.